The star-switched MMC (SSMMC): a hybrid VSC for HVDC applications - Woldegiorgis, Dereje Lemma; Outram, John; Amankwah, Emmanuel K.; Trainer, David; Clare, Jon C. (2016)
This paper presents a new hybrid VSC topology (the Star-Switched MMC) – suitable for HVDC applications. The basic structure and operating principles of the topology are described. Control strategies that regulate the power exchanged between the VSC, the AC network and the DC network are presented. A modulation strategy ensuring appropriate switching of the individual chain-link sub-modules and a capacitor voltage balancing algorithm that ensures the capacitor voltages are maintained within the required tolerance are discussed. Results from a simulation model are presented to validate the expected performance of the converter and the proposed control schemes.